Legitimisation Strategies in Covid-19 Related Discourse : Comparing Health Officials and Conspiracy Theorists - Vainio, Anniina (My University, 2022)
This thesis is focused on the use of legitimisation strategies in Covid-19 related online discourse. Legitimisation strategies are used in discourse to create credibility and justify an action or a message. The purpose of this thesis is to find out what type of legitimisation strategies are used on two different types of news websites. The websites introduce two perspectives to this study. The data comes from the Natural News website, that represents a conspiracy theory point of view, and the World Health Organisation News website, that represents an official health agency point of view. Random sampling is used as a method to collect five articles from each website. The research strategy in this thesis is mixed methods research, as both qualitative and quantitative research is combined. The approach to analysing the data is based on discourse analysis, as this thesis studies language as a social practice, as discourse. The data is analysed by conducting content analysis on the data by studying the legitimisation strategies from the collected data and interpreting the meanings behind the strategies. The analysis is finalised by comparing the findings between the two datasets. According to the findings of this thesis use of legitimisation strategies to create credibility was found from both datasets. A total of 144 cases of use were found. However, a difference was discovered in the use of the strategies. The findings indicate that WHO News used legitimisation strategies that were based on rationality and expert authority the most, and strategies that were based on hypothetical future and emotions the least. Natural News was discovered to use legitimisation strategies that were based on hypothetical future and emotions the most, and strategies that were based on rationality and expert authority the least. Therefore, a significant contrast was discovered between the two sources of data. A different purpose and a different tone and style of communicating between WHO News and Natural News is discussed as a possible factor affecting the found differences and as a meaning of the results. The interpretation of the meaning of the results indicated that the purpose of WHO News is to convey factual and scientific information, whereas the purpose of Natural News is to express opinions and influence. Lastly, the limitations regarding this study and possibilities for further research are discussed.
Keywords: legitimisation, credibility, conspiracy theory, discourse analysis, Covid-19